DESIGN AND IMPLEMENTATION OF AN EEG-BASED BCI PROSTHETIC LOWER LIMB USING RASPBERRY PI 4 - Drăgoi, Marius-Valentin; Hadăr, Anton; Goga, Nicolae; Grigore, Lucian-Ștefăniță; Ștefan, Amado; Ali, Haider Abdullah (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2023)
This paper presents a design and implementation of a mind-controlled prosthetic lower limb prototype to help leg amputees who lost their lower limbs due to different reasons. The system contains a prosthetic lower limb equipped with two servomotors, a motor driver module, a Raspberry Pi, a neuro-headset, and a computer. The prosthetic lower limb prototype is a low-cost 3D-printed prosthetic controlled by brain signals. The prototype has two degrees of freedom for the knee and ankle, which are flexion, extension, plantarflexion, and dorsiflexion. The implemented prototype has been tested on a healthy subject in real-time using the detected brain signals.